Decreased Default Mode Network connectivity correlates with age-associated structural and cognitive changes - Vidal-Piñeiro, Didac; Valls-Pedret, Cinta; Fernández-Cabello, Sara; Arenaza-Urquijo, Eider M.; Sala-Llonch, Roser; Solana, Elisabeth; Bargalló, Núria; Junqué, Carme; Ros, Emilio; Bartrés-Faz, David (Frontiers in Aging Neuroscience, 2014)
Ageing entails cognitive and motor decline as well as brain changes such as loss of grey and white matter integrity, neurovascular and functional connectivity alterations. Regarding connectivity, reduced resting-state fMRI connectivity between anterior and posterior nodes of the Default Mode network (DMN) relates to cognitive function and has been postulated to be a hallmark of ageing. However, the relationship between age-related connectivity changes and other neuroimaging-based measures in ageing is fragmentarily investigated. In a sample of 116 healthy elders we aimed to study the relationship between antero-posterior DMN connectivity and measures of white matter integrity, grey matter integrity and cerebral blood flow, assessed with an arterial spin labeling sequence. First, we replicated previous findings demonstrating DMN connectivity decreases in ageing and an association between antero-posterior DMN connectivity and memory scores. The results showed that the functional connectivity between posterior midline structures and the medial prefrontal cortex was related to measures of white matter and grey matter integrity but not to cerebral blood flow. Grey and white matter correlates of anterio-posterior DMN connectivity included, but were not limited to, DMN areas and cingulum bundle. These results resembled patterns of age-related vulnerability which was studied by comparing the correlates of antero-posterior DMN with age-effect maps. These age-effect maps were obtained after performing an independent analysis with a second sample including both young and old subjects. We argue that antero-posterior connectivity might be a sensitive measure of brain ageing over the brain. By using a comprehensive approach, the results provide valuable knowledge that may shed further light on DMN connectivity dysfunctions in ageing.